Post-COVID-19 metabolic syndrome: a new challenge for nursing care - Cruz Neto , João; Frota Cavalcante , Tahissa; de Carvalho Félix , Nuno Damácio (Investigación y Educación en Enfermería, 2023)
In crisis scenarios, the professions that have the essence of caring for are highlighted. In this sense, during the COVID-19 pandemic, nursing played a key role in the identification, testing, care and rehabilitation of patients. It was through this profession that many clients were fully assisted in the process of illness/rehabilitation, revealing the importance of the category for the health system; a fact that also persists in a post-COVID scenario. COVID-19 led to the collapse of global health with high rates of mortality and hospital morbidity, generating an estimated 18.2 million deaths around the world. Nevertheless, it is known that COVID-19 is a respiratory disease with vascular implications that interact with cardiometabolic factors such as oxidative stress, endothelial dysfunction, insulin resistance, atherosclerosis, overweight, increased body fat and alterations in the microbiome, leading to systemic complications and death.